Pasang Surut Perdagangan Pada Masa Kesultanan Palembang Tahun 1804-1821 - Rima Agri Triacitra; Nor Huda; Nyimas Umi Kalsum (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2021)
This article examines the ups and downs of trade during the Palembang Sultanate from 1804-1821. This historical study is vulnerable to time from the time of the Palembang Sultanate to the end of the Palembang Sultanate. This study used descriptive qualitative method. The emergence of the Palembang Sultanate in the 17-19th century has provided the background for the life of the Palembang people. Palembang as the center. The government of the Sultanate of Palembang has a very strategic location because it is at the confluence of the Musi River, thus providing benefits for the development of the area, especially in the economic sector. In the development of this trade, there were frequent ups and downs and ups and downs caused by the many conflicts that occurred in the Palembang Sultanate. Keywords: Keraton, Sultanate of Palembang, Trade